Uganda Economic Update, February 2015 : The Growth Challenge--Can Ugandan Cities Get to Work? - World Bank (World Bank, Washington, DC, 2015)
This Fifth Edition of the Uganda Economic Update presents evidence that if the urbanization process is well managed, it has the potential to stimulate economic growth and to provide productive jobs for a greater proportion of Uganda’s young and rapidly expanding population. In many countries across the world, the growth of cities has stimulated the establishment and expansion of productive businesses by reducing the distance between suppliers and customers. The growth of cities has also facilitated provision of social services and infrastructure through economies of scale. These positive effects from urbanization are already visible in Uganda since the poverty rate is seven percentage points lower in urban areas than in rural areas. Most of the recent job creation is found in cities, and social indicators are also better in urban areas, especially in education and health.